Risks of Civic Activity and Motivation for Civic Engagement in Contemporary Lithuanian Societ - Žiliukaitė, Rūta (Sociologija. Mintis ir veiksmas, 2010)
The data of longitudinal research project “Civic Empowerment Index of Lithuanian society” show that more than a half of Lithuania’s population thinks that it is likely for an individual who initiates and takes an active part in civic activity to suffer damage due to his/her civic engagement. Analysis presented in this article reveals that people, who do not participate in civic activities, and those, who take and active part in it, do not differ in regard of their attitudes towards likelihood to encounter various threads by being engaged in civic activity. Data also show that people who are more active members of civil society more often indicate that they personally experienced such damage than those, who participate in civic activities rarely. Taking into account these results, the article aims to answer two questions. First, why do people, who have an experience of suffering damages due to their civic engagement or who think that it is likely to suffer such damages in contemporary Lithuanian society, continue to take an active part in these activities? Second, how damages, perceived by majority of the population, may restrict the involvement of people into collective action?